Equaliberty under pressure. Challenges for educational science and (social) paedagogy - Fabian Kessl (Social Work and Society)
Equality is the basic premise of democracy. At the same time its actual realisation in existing democracies has always been limited. The relation between equality and democracy and the fact that historically its substantiation has never been fully achieved reveals the historically equiprimordial nature of equality and liberty (Balibar 2010/2012). Since the 18th century this equiprimordial nature, as an "equation of human and citizen" (Balibar 2010/2012, p. 89; own translation), constitutes the ideal of the emerging bourgeois society (bürgerliche Welt). The necessity of a boundedness of equality and liberty has been known since ancient attempts to establish the Ï€ÏŒÎ»Î¹Ï‚ (polis). However, in the city state of Athens an Attic man's liberty as a citizen, meaning as a political agent, was not bound to the concept of equality as a human right, but to his exclusive power position in the household (Î¿á¼¶ÎºÎ¿Ï‚ (oikos). The male Attic citizen's control over reproduction, care and relationships in the private household guaranteed the necessary foundation for his political agency and acting in (political) liberty. Hence, the political participation of an Attic man was bound to securing his livelihood. The separation of public and private sphere as a principle is still effective in bourgeois society (Rosenbaum/Timm 2008). However, the Attic polis and bourgeois society of the modern world are entirely different: Attic citizenry was particular, as only grown and free men enjoyed the privilege of being part of it. A universal conception of mankind as citizens (human right) did not exist yet. Therefore the polis as a political public sphere, and hence as a space of liberty, always remained limited. The establishment of Bourgeois society did not bring an end to this structural logic. In parts of Switzerland it could be experienced first hand just a few years ago: In 1989 the community of Appenzell Innerrhoden which was represented exclusively by men defeated a motion for women's suffrage in a direct vote.